2017
DOI: 10.18869/acadpub.joge.1.4.47
|View full text |Cite
|
Sign up to set email alerts
|

The role of communication skills, social support and daily spiritual experiences in predicting loneliness feeling of the elderly

Abstract: Introduction: Attention and concentration on predictor variables of loneliness feeling in the elderly is an introduction to successful reduction of loneliness feeling and decreasing its serious consequences. The purpose of this study was to determine the role of communication skills, social support and daily spiritual experiences in predicting loneliness feeling of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…With increasing age, some of these communication skills decrease due to physical problems and disabilities caused by old age and distance from society. 15 In relation to the marital status, the present study showed that married elderly have better communication skills than those who have lost their spouses. The results of our research are in line with the findings of Yusefi et al 14 and Qolizadeh et al 35 but not with the study of Ebadi 36 and Khatib Zanjani and Moharreri.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…With increasing age, some of these communication skills decrease due to physical problems and disabilities caused by old age and distance from society. 15 In relation to the marital status, the present study showed that married elderly have better communication skills than those who have lost their spouses. The results of our research are in line with the findings of Yusefi et al 14 and Qolizadeh et al 35 but not with the study of Ebadi 36 and Khatib Zanjani and Moharreri.…”
Section: Discussionmentioning
confidence: 52%
“…The findings showed that the mean and SD of the communication skills of the hospitalized elderly is 129.09 ± 12.60. In the study of Hosseini Ramaghani et al, the mean and SD of communication skill scores of the senior participants was 108.30 ± 34.54, 15 which was 114.51 ± 9.93 in Mojadam et al's study. 13 These results indicate that the communication skills of the elderly participating in this study are at a favorable level (129.09 ± 12.60).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations